Rethinking Community Resilience : The Politics of Disaster Recovery in New Orleans - Go, Min Hee (Book collections on Project MUSE., 2021)
Explores the unintended consequences of civic activism in a disaster-prone cityAfter Hurricane Katrina, thousands of people swiftly mobilized to rebuild their neighborhoods, often assisted by government organizations, nonprofits, and other major institutions. In Rethinking Community Resilience, Min Hee Go shows that these recovery efforts are not always the panacea they seem to be, and can actually escalate the city's susceptibility to future environmental hazards. Drawing upon interviews, public records, and more, Go explores the hidden costs of community resilience. She shows that--despite good intentions--recovery efforts after Hurricane Katrina exacerbated existing race and class inequalities, putting disadvantaged communities at risk. Ultimately, Go shows that when governments, nonprofits, and communities invest in rebuilding rather than relocating, they inadvertently lay the groundwork for a cycle of vulnerabilities. As cities come to terms with climate change adaptation--rather than prevention--Rethinking Community Resilienceprovides insight into the challenges communities increasingly face in the twenty-first century.